TEACHERS' REFLECTION ON TEACHING ENGLISH AS THE REQUIRED COURSE - Dwi Wulandari (Proceedings of ISELT FBS Universitas Negeri Padang, 2015)
Teaching English in university setting for non-English department is many times considered to be a frustrating experience, with th: teachers' complaining of the difficulties in managing the class. both because of the many classes to teach and the big number of the students in the class. This article is aimed at taking a look at how teachers are able to reflect on their own teaching in a way that they are searching within their experiences of what could be best taken by their students in leaming English. This article will be focused on 18 English teachers rvho are asked to fill in questionnaires about their own teaching practice, the reasons behind the practice. the problems they encounter, and their golls in teaching, as well as their expectations. The results of the study show the fact that the teachers are teaching grammar as the main material though they are aware of its being ineffective, and yet they seem to be unable or unwilling to explore other options. There are also certain issues that the teachers address such as the goals of targeted competence and the abundance of available source in internet. All of the teachers share the same expectations of the possibility in teaching the English skill independently. including speaking and writing skills. However, they reluctantly think of ways to realize such expectations as they felt that they are being restricted with the design of English classes.